Perspektif Ibu Dalam Memilih Kontrasepsi IUD : Scoping Review - Intan Pramesti; Machfudloh Machfudloh; Is Susiloningtyas (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Background: One type of long-term contraception, namely the IUD which has high effectiveness, can last 5 to 10 years, but the number of acceptors is still low compared to other methods. The coverage of active IUD contraception participants in 2020 reached 11.91% of all active KB active participants, the low coverage of IUD contraception was due to several factors such as the wrong mother's perspective/perception about IUD contraception and the mother's lack of knowledge about IUD contraception and the lack of husband's support. If it is not handled, the impact that will arise is that users of IUD contraceptive acceptors can decrease. Objective: To review the literature on the mother's perspective in choosing the IUD contraception. Methods: The method in writing this article is a review of the literature contained in the database of health journals, namely PubMed, ProQuest, and Google Scholar. The selected articles are based on full text, open access, in English and Indonesian published based on the last 5 years (2017 – 2021). Results: 35 articles from Google Scholar, 10 articles from pubmed, and 8 articles from ProQuest. The results obtained that there is a significant relationship between the mother's perception or views in choosing the IUD contraception. Conclusion: The conclusion is that knowledge and perceptions of mothers about IUD contraception affect the choice of contraception and husband's support is also very necessary in the selection of contraceptives by providing support and attention will help mothers in choosing contraceptives that they understand, including the advantages and disadvantages, risks of the IUD contraceptive method.